3-D shape analysis of palatal surface in patients with unilateral complete cleft lip and palate - Rusková, Hana; Bejdová, Sárka; Peterka, Miroslav; Krajíček, Václav; Velemínská, Jana (Journal of cranio-maxillo-facial surgery, 2014)
Facial development of patients with unilateral complete cleft lip and palate (UCLP) is associated with many problems including deformity of the palate. The aim of this study was to evaluate palatal morphology and variability in patients with UCLP compared with Czech norms using methods of geometric morphometrics. The study was based on virtual dental cast analysis of 29 UCLP patients and 29 control individuals at the age of 15 years. The variability of palatal shape in UCLP patients was greater than that in nonclefted palates. Only 24% of clefted palates fell within the variability of controls. The palatal form of UCLP patients (range from 11.8 to 17.2 years) was not correlated with age. Compared with control palates, palates of UCLP patients were narrower, more anteriorly than posteriorly. Apart from the praemaxilla region, they were also shallower, and the difference increased posteriorly. The UCLP palate was characterised by the asymmetry of its vault. The maximum height of the palatal vault was anterior on the clefted side, whereas it was posterior on the nonclefted side. The slope of the UCLP palate was more inclined compared with the control group. The praemaxilla was therefore situated more inferiorly.
Keywords: maxila; rozštěp rtu; Palate; Anatomic Variation; anatomická značka; Cleft Palate; anatomická variace; počítačové zpracování obrazu; mladiství; rozštěp patra; Dense correspondence analysis; mužské pohlaví; Cephalometry; Cleft Lip; 3-D geometric morphometrics; Models, Dental; Palatal shape; dítě; Plastic Surgery Procedures; Child; zubní modely; věkové faktory; Humans; Anatomic Landmarks; Surface scanning; zobrazování trojrozměrné; uživatelské rozhraní počítače; Imaging, Three-Dimensional; Image Processing, Computer-Assisted; Age Factors; Unilateral cleft of lip and palate; patro; User-Computer Interface; kefalometrie; zákroky plastické chirurgie; Adolescent; lidé; Male; Maxilla